Repeatability and relative validity of a quantitative food-frequency questionnaire among French adults - Emmanuel Barrat; Nicolas Aubineau; Matthieu Maillot; Élodie Derbord; Pauline Barthes; Jean-François Lescuyer; Nathalie Boisseau; Sébastien L. Peltier (Food & Nutrition Research, 2012)
Background: A 50-item self-administered food frequency questionnaire (FFQ) was developed for French adults, to assess the intake of energy, 10 macronutrients, 11 vitamins, and 11 minerals, and to be used in the context of a medical consultation. Objective: To assess the repeatability and relative validity of this FFQ compared to a 7-day diet record (7-DR). Design: A total of 54 and 100 French adults were included in the repeatability and validation studies, respectively. Repeatability was assessed using two FFQs, the second carried out 3 weeks after the first. In the validation study, subjects first completed the FFQ, then the 7-DR the following week. Energy and nutrient intakes were compared using Pearson correlation. The degree of misclassification by the FFQ, compared to the 7-DR, was calculated by a contingency table of quintiles. Bland–Altman plots assessed the correlation between FFQ and 7-DR across the intake range. Results: Repeatability for intake, explored by Pearson correlation, was 0.62–0.90 (median: 0.81). Relative validity, as determined by Pearson correlation for the nutrient intake derived from the FFQ and 7-DR, was 0.36–0.80 (0.64). The FFQ tended to report higher fiber and micronutrient intake than 7-DR. Misclassification into opposite quintiles ranged 0–6% (1%), whereas classification into same or adjacent quintiles ranged 59–83% (74%). Bland–Altman plots showed good agreement for most nutrients across the range of intake. Conclusion: This new FFQ showed a high repeatability and good relative validity, and thanks to its short length, should be a useful tool for rapidly evaluating the nutrient intake of French adults.